Venture Capital: World-Wide Scenario - Ghai, S. K.; Kaushik, Priyanka (Journal of Commerce and Trade, 2016)
Venture capital (popularly known as VC) investment has become one of the most swiftly growing investment approaches world-wide, especially in developing countries. The contributing features to this growth are the latest economic as well as legally permissible changes. Various governments have provided purposeful operational and well-designed autonomy to institutions while at the same time closely observing them by framing numerous rules and regulations that lay down various ways for the investment. In other words, it can be said that the laws-by laws are still investment-friendly and offers various benefits in the shape of tax reforms for both domestic as well as foreign investors.